2003
DOI: 10.1021/es0201451
|View full text |Cite
|
Sign up to set email alerts
|

DDT-Related Compounds Bound to the Nonextractable Particulate Matter in Sediments of the Teltow Canal, Germany

Abstract: Sediment samples of the Teltow Canal (Berlin, Germany) were analyzed with respect to extractable and nonextractable organic compounds. The study focused on the identification and quantitation of bound 2,2-bis(chlorophenyl)-1,1,1-trichlorethane (DDT) residues in order to obtain further information about the fate of DDT-derived compounds within the particulate matter of the aquatic environment. Various chemical degradation techniques and a complementary online pyrolysis-GC/MS method were applied to the pre-extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 31 publications
(29 reference statements)
5
59
2
Order By: Relevance
“…These included, freshwater sediments contaminated with BZTs from the Pawtuxet River (PR) (Reddy et al, 2000a) and from a control site (Station 3), upstream of the chemical plant that released the BZTs into the river ( Figure 5.2 insert), and freshwater sediments contaminated with DDT from Teltow Canal (TC) (Schwarzbauer et al, 2003). The Palos Verdes (PV) shelf is a coastal marine site that also has a history of DDT contamination (Eganhouse et al, 2000) and thus for comparison, sediments from this site were analyzed.…”
Section: Study Area and Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…These included, freshwater sediments contaminated with BZTs from the Pawtuxet River (PR) (Reddy et al, 2000a) and from a control site (Station 3), upstream of the chemical plant that released the BZTs into the river ( Figure 5.2 insert), and freshwater sediments contaminated with DDT from Teltow Canal (TC) (Schwarzbauer et al, 2003). The Palos Verdes (PV) shelf is a coastal marine site that also has a history of DDT contamination (Eganhouse et al, 2000) and thus for comparison, sediments from this site were analyzed.…”
Section: Study Area and Samplesmentioning
confidence: 99%
“…By examining the associations of organic compounds to MOM we aimed to make predictions regarding their long-term fate. In the case of hydrophobic organic contaminants (HOCs) this is of interest as previous studies have shown that certain HOCs or their metabolites can bind to MOM in sediments (Beller et al, 1998;Richnow et al, 1994;Reddy et al, 2000;Schwarzbauer et al, 2003), but this process is difficult to follow and quantitatively constrain. Binding to sedimentary MOM has the potential to influence the bioavalability, toxicity and transport of HOCs, and thus understanding these processes is of great interest from an environmental and human health perspective.…”
Section: General Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of DDT-related pollutants to the nonextractable matter of sediments from the Teltow Canal has been reported recently [21]. This study was primarily initiated to quantify concentrations of bound 2,2-bis(chlorophenyl)-1,1,1-trichloroethane (DDT) residues in order to obtain further information about the fate of DDT-derived compounds within the particulate matter of the aquatic environment.…”
Section: Introductionmentioning
confidence: 99%